Reduced Self-Control after 3 Months of Imprisonment; A Pilot Study - Meijers, Jesse; Harte, Joke M.; Meynen, Gerben; Cuijpers, Pim; Scherder, Erik J. A. (Frontiers in Psychology, 2018)
Prison can be characterized as an impoverished environment encouraging a sedentary lifestyle with limited autonomy and social interaction, which may negatively affect self-control and executive function. Here, we aim to study the effects of imprisonment on self-control and executive functions, and we report the change in neuropsychological outcome after three months of imprisonment. Participants were 37 male inmates in a remand prison in Amsterdam, the Netherlands, who completed six tests of a computerized neuropsychological test battery (the CANTAB) in the first week of arrival. Participants were retested after three months of imprisonment. Change in performance was tested using the Wilcoxon Signed-Rank test. After three months of imprisonment, self-control risk taking significantly increased (measured as an increase in the proportion of available points used for betting) and attention significantly deteriorated (measured as increased variability in reaction times on a sustained attention task), with large to medium effect sizes. In contrast, planning significantly improved (measured with a task analogue to the Tower of London) with a medium effect size. Our study suggests that three months of imprisonment in an impoverished environment may lead to reduced self-control, measured as increased risk taking and reduced attentional performance. This is a significant and societally relevant finding, as released prisoners may be less capable of living a lawful life than they were prior to their imprisonment of, and may be more prone to impulsive risk-taking behaviour. In other words, the impoverished environment may contribute to an enhanced risk of reoffending.